Differences in the Clinical Characteristics of Rapid Response System Activation in Patients Admitted to Medical or Surgical Services - Lee, Yeon Joo; Lee, Dong Seon; Min, Hyunju; Choi, Yun Young; Lee, Eun Young; Song, Inae; Yoon, Yeonyee E.; Kim, Jin Won; Park, Jong Sun; Cho, Young-Jae; Lee, Jae Hyuk; Suh, Jung-Won; et al. (Journal of Korean medical science, 2017)
Variability in rapid response system (RRS) characteristics based on the admitted wards is unknown. We aimed to compare differences in the clinical characteristics of RRS activation between patients admitted to medical versus surgical services. We reviewed patients admitted to the hospital who were detected by the RRS from October 2012 to February 2014 at a tertiary care academic hospital. We compared the triggers for RRS activation, interventions performed, and outcomes of the 2 patient groups. The RRS was activated for 460 patients, and the activation rate was almost 2.3 times higher for surgical services than that for medical services (70% vs. 30%). The triggers for RRS activation significantly differed between patient groups (P = 0.001). They included abnormal values for the respiratory rate (23.2%) and blood gas analysis (20.3%), and low blood pressure (18.8%) in the medical group; and low blood pressure (32.0%), low oxygen saturation (20.8%), and an abnormal heart rate (17.7%) in the surgical group. Patients were more likely classified as do not resuscitate or required intensive care unit admission in the medical group compared to those in the surgical group (65.3% vs. 54.7%, P = 0.045). In multivariate analysis, whether the patient belongs to medical services was found to be an independent predictor of mortality after adjusting for the modified early warning score, Charlson comorbidity index, and intervention performed by the RRS team. Our data suggest that RRS triggers, interventions, and outcomes greatly differ between patient groups. Further research is needed to evaluate the efficacy of an RRS approach tailored to specific patient groups.